2023
DOI: 10.3389/fanim.2023.1188874
|View full text |Cite
|
Sign up to set email alerts
|

Rumen microbiome response to sustained release mineral bolus supplement with low- and high-quality forages

Abstract: IntroductionLimited forage quantity and quality are challenges faced in livestock production systems in semi-arid rangelands of the western United States, particularly when livestock face stressors such as cold weather or have increased nutritional requirements such as during pregnancy and lactation. To meet livestock nutrient requirements, producers frequently provide supplemental nutrition, however there is limited knowledge regarding the effects of these practices on the rumen microbiome in these environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…The sufficient utilization of fibrous forages by ruminants relies on the rumen, the largest anaerobic stomach chamber, which harbors a complex and dynamic functional microbe community that plays decisive roles in the efficient biodegradation of ingested feed and synthesis of microbially derived nutrients (Membrive, 2016). Previous studies have explored the ruminal microbial differences between animals fed low-quality and high-quality forage-based diets, and found dramatic variations in the abundances of core rumen microbes with characteristics that are important for the decomposition of structural and non-structural carbohydrates (Wei et al, 2021;Zhu et al, 2022;Eberly et al, 2023). For example, Liu et al found higher proportions of the fiber-degrading Butyrivibrio and Prevotella in the alfalfa diet than in the rice straw diet, and a reverse pattern of unclassified Ruminococcaceae (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The sufficient utilization of fibrous forages by ruminants relies on the rumen, the largest anaerobic stomach chamber, which harbors a complex and dynamic functional microbe community that plays decisive roles in the efficient biodegradation of ingested feed and synthesis of microbially derived nutrients (Membrive, 2016). Previous studies have explored the ruminal microbial differences between animals fed low-quality and high-quality forage-based diets, and found dramatic variations in the abundances of core rumen microbes with characteristics that are important for the decomposition of structural and non-structural carbohydrates (Wei et al, 2021;Zhu et al, 2022;Eberly et al, 2023). For example, Liu et al found higher proportions of the fiber-degrading Butyrivibrio and Prevotella in the alfalfa diet than in the rice straw diet, and a reverse pattern of unclassified Ruminococcaceae (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%